Evaluating and Analyzing The Transposition Factor In Al- Musayyib Technical College to Setting The Optimal Tilt Angle for Fixed And Seasonal Orientation - Hameed Jaseem, Bushra Majed; Sadiq Al-Kafaji, Muhammed Salah; Abdulsadda, Ahmed T (Salud, Ciencia y Tecnología - Serie de Conferencias, 2024)
The transposition factor (TF) enhances the photovoltaic (PV) systems' capacity to generate output power. The observed phenomenon denotes the alteration in power production resulting from the inclination of the collector plane. The objective of this study is to assess and compare the effects of two different types of orientation, fixed titled plane and seasonal tilt adjustment, on the power output of a photovoltaic system located in the electrical engineering technologies department at Al- Musayyib Technical College (MTC) in Iraq. The specific coordinates of the location are latitude 32° 46′ 59.99″ N and longitude 44° 19′ 0.01 E . The simulation will be conducted using the Perez model in PVSYST software, focusing on a standalone system with a power capacity of 3000 Wp. The results that were displayed are dependent on the highest (TF), the optimal tilt angle for a fixed tilted plane is 28o, and for seasonal tilt adjustment is (12o in summer and 50o in winter). In addition, the results showed that applying the seasonal tilt adjustment was preferable to using a fixed titled plane in this location to gain the maximum amount of system production power while maintaining a low cost